Influência de protocolos contínuos e descontínuos com diferentes velocidades iniciais na determinação da velocidade pico em corrida - Alves, Júlio César Camargo (2013)
The maximum speed obtained in an incremental test called peak speed (Vpeak) and thresholds related to blood lactate concentrations (Lactate Threshold - LL; Anaerobic Threshold - AT) are used by researchers and coaches since it present high correlations with endurance performances, and can be used as a good parameter for training prescription and monitoring. However some factors related to the protocol may influence the determination of these variables. Thus, the objective of this study was to investigate the influence of continuous and discontinuous protocols with different initial speeds on the determination of Vpeakand LL in running, and correlate these parameters with a 10km running performance. Participated voluntarily in the study 17 healthy male runners (35.2 ± 5.2 years; body mass of 73.9 ± 5.1 kg; height of 176.0 ± 1.0 cm; body mass index BMI of 23.8 ± 1.7 kg.m-2; and body fat - % of 9.7 ± 2.0 %), with a background in 10 km performances (average time of 48.1 ± 6.2 min, varying from 39 to 60 min). Participants performed four maximal incremental running tests using a multiprogrammable treadmill (Inbramed Super ATL, Porto Alegre - Brazil) preceded by a three minutes warming at 6 km.-1; it was tested the beginning of the protocol at 8 km.h-1 (Cont8) and 10 km.h-1 (Cont10) with increments of 1 km.h-1 every three minutes. The discontinuous protocol was similar to the continuous except for additional 15 s pauses between each stage for blood sampling (25µl) of the earlobe, and thereafter the determination of blood lactate concentration, characterized as a discontinuous protocol (Descont8 and Descont10).To determine LL speeds (vLL) it was used the following methods: Dmáx, fixed concentration of 3.5 mmol.L-1, and visual inspection. Participants also performed two 10 km running performances in a running track, it was considered for the analysis the best mean speed (Vmean) of the performance. Descriptive statistics was used for data presentation (mean ± standard deviation, SD).Data normality was tested by the Shapiro-Wilk test. The tests were compared by the Anova of repeated measure with Bonferroni adjustment for multiple comparions. The sphericity assumption was verified by the Mauchly test and when violated, the degrees of freedom were corrected using estimates of sphericity by the Greenhouse-Geisser test. The relations between Vmean obtained in performance with Vpeak and vLL determined by different methods were demonstrated by Pearson's correlation coefficient (r), standard error of estimate (SEE) and linear regression analyses. It was adopted a significance level of P < 0.05. The results showed that Vpeak was not influenced by incremental protocol with different initial speeds (Cont8 = 15.4 ± 1.5 km.h-1; Cont10 = 15.2 ± 1.6 km.h-1) but for different protocol types (Descont8 = 13.1 ± 1.1 km.h-1; Descont10 = 13.8 ± 1.1 km.h-1); furthermore there was a significant difference between the vLL determined by the fixed concentration method and the vLL determined by the other methods for the Descont8 protocol. The determination of Vpeak by the protocol Cont8(r = 0.92) and the vLL determined by the methods of fixed concentration (r = 0.83 and 0.81) and Dmáx (r = 0.81 and 0.81) independent of the v incremental protocol initial speed, presented the highest values of correlation with the 10 km running performance. In conclusion, Vpeak was not influenced by different speeds, but for different different protocol types (continuous vs discontinuous), further, the protocol Cont8presented the best correlation coefficient with the 10 km running performance. Regarding vLL, different protocols altered the Dmax method, furthermore, the fixed concentration and Dmax presented the higher correlation with 10 km running performance regardless of the initial speed used in the incremental protocols